Preparation method of hydrogen permeation foil
Through the mixing of nanomaterials and the composite technology of platinum foil, an efficient hydrogen permeability foil is formed, which solves the problems of complex equipment, high energy consumption and easy hydrogen embrittlement in the existing technology, and achieves an efficient, stable and economical hydrogen separation effect.
Patent Information
- Application Number
- CN202510039527.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The existing hydrogen separation technology has problems such as complex equipment, high energy consumption, and limited separation efficiency, and palladium foil is prone to hydrogen embrittlement during long-term use, which limits its large-scale application.
Nanosilicon, nanocarbon and nanohollow carbon fibers are mixed in a specific proportion, bonded with silicon sol through ultrasonic dispersion, forming a support body, and composited with high-purity platinum foil, and a foil with high-efficiency hydrogen permeability is formed by hot pressing and annealing.
It improves the comprehensive performance of hydrogen permeable foil, enhances hydrogen transmission stability and overall structural strength, reduces energy consumption and equipment losses, and extends service life. It is suitable for hydrogen separation applications in the energy and chemical fields.
Smart Images

Figure CN119840280A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of material science, and in particular to a method for preparing a hydrogen permeable foil. Background Art
[0002] In today's energy and chemical industry, with the growing demand for clean energy and the emergence of demands for industrial waste gas treatment, efficient hydrogen separation and purification technology has become increasingly critical. Traditional hydrogen separation methods, such as pressure swing adsorption and cryogenic distillation, have met some industrial needs to a certain extent, but they have many disadvantages such as complex equipment, high energy consumption, and limited separation efficiency.
[0003] From an energy perspective, fuel cells are a highly potential clean energy conversion device, and their stable and efficient operation is highly dependent on the supply of high-purity hydrogen. However, the hydrogen currently prepared is often mixed with impurity gases such as nitrogen, carbon dioxide, and carbon monoxide, which seriously affects the performance and life of fuel cells. In chemical production, many reaction byproduct gases contain a certain proportion of hydrogen. If it can be effectively separated, purified, and reused, it can not only reduce the cost of raw materials, but also reduce resource waste and environmental pollution.
[0004] Hydrogen permeable foil has emerged as an emerging hydrogen separation technology. Its principle is based on the special adsorption, diffusion and permeation properties of certain metals and composite materials for hydrogen, which can allow hydrogen to selectively permeate under certain conditions while blocking other gases. Early research focused on single metal foils, such as palladium foil, but palladium metal is expensive, and pure palladium foil is prone to hydrogen embrittlement and other problems in long-term use, which limits its large-scale application.
[0005] In recent years, with the rapid development of nanotechnology, researchers have begun to explore the introduction of nanomaterials into the preparation of hydrogen permeable foils. Nano silicon, with its high specific surface area, can provide abundant sites for gas adsorption and diffusion; nano carbon has unique electrical properties and can play an auxiliary role in the process of hydrogen adsorption and conduction; the hollow structure of nano hollow carbon fiber is like a natural gas transmission "channel", and the three are expected to work together to improve the comprehensive performance of hydrogen permeable foils. At the same time, combined with the catalytic advantages of precious metals such as platinum, by optimizing the preparation process, overcoming the shortcomings of traditional hydrogen separation technology and meeting the increasingly stringent industrial and energy application needs have become the key technical issues that this invention is committed to solving. Summary of the invention
[0006] 1. Technical issues to be resolved
[0007] In view of the deficiencies of the prior art, the present invention provides a method for preparing a hydrogen permeable foil, which solves the problems raised in the above background technology.
[0008] (II) Technical solution
[0009] In order to achieve the above-mentioned purpose, the present invention specifically adopts the following technical solutions:
[0010] A method for preparing a hydrogen permeable foil comprises the following steps:
[0011] S1. Preparation of support:
[0012] Mix nano-silicon, nano-carbon and nano-hollow carbon fiber in an organic solvent ethanol at a ratio of 5:3:2, and use an ultrasonic dispersion device to ultrasonically treat the mixed solution, with an ultrasonic power between 100-500W and an ultrasonic time of 30-90 minutes to ensure that each nanomaterial is evenly dispersed;
[0013] Slowly add silica sol to the dispersed solution while stirring continuously. The stirring speed is controlled between 300-800rpm. Stir continuously for 2-4 hours to fully mix the silica sol and the nanomaterial.
[0014] The mixed solution is coated on the substrate material by dipping, spraying or spin coating to form a precursor of the support body, and the coating thickness can be between 1-10 μm;
[0015] The coated precursor is placed in an oven for drying at a temperature between 80 and 120°C for 12 to 24 hours to volatilize the organic solvent and initially solidify the binder;
[0016] The dried support precursor is then placed in a high-temperature furnace for sintering at a temperature between 400-600°C for 2-6 hours. During the sintering process, the silica sol further reacts to form a stable structure, and the nanomaterials are more tightly bonded, thereby forming a support with good performance.
[0017] S2. Assembly of hydrogen permeable foil:
[0018] The prepared support is compounded with the platinum foil, and the support is tightly combined with the platinum foil by hot pressing at a pressure of 1-5 MPa and a temperature of 300-500°C. The hot pressing time is 30-90 minutes, so as to ensure good interface bonding between the support and the platinum foil, which is conducive to the transmission of hydrogen;
[0019] S3, post-processing:
[0020] Annealing the assembled hydrogen permeable foil at a temperature between 600 and 800° C. for 1 to 3 hours. Annealing in a hydrogen atmosphere can further activate the surface of the platinum foil and improve its ability to adsorb and catalyze decomposition of hydrogen.
[0021] The prepared hydrogen permeable foil was subjected to a performance test. A mixed gas containing hydrogen was passed into one side of the hydrogen permeable foil using a mixed gas simulation device, and the permeated gas was collected on the other side. The content and purity of hydrogen in the permeated gas were detected by gas chromatography and other analytical methods to evaluate the performance of the hydrogen permeable foil.
[0022] Furthermore, the base material is a ceramic sheet or a metal sheet.
[0023] Furthermore, the platinum foil has a purity of more than 99.95%, and an initial thickness of the platinum foil is between 10-100 μm. It serves as the main functional layer for hydrogen permeation because platinum has good adsorption and catalytic decomposition capabilities for hydrogen, and can promote the separation of hydrogen in the mixed gas.
[0024] Furthermore, the mass fraction of the silica sol is between 10% and 30%.
[0025] Furthermore, during the ultrasonic treatment, there is a 5-minute pause every 15 minutes to prevent local overheating of the solution due to continuous ultrasonication, which may affect the dispersion effect and structural stability of the nanomaterials. At the same time, the solution temperature is regularly checked to maintain it between 30-50°C.
[0026] Furthermore, the immersion method is specifically as follows: slowly immersing the substrate material into the mixed solution at a speed of 1-3 cm / min for 30-60 seconds to ensure that the solution is evenly attached to the surface of the substrate; the spraying pressure of the spraying method is controlled at 0.2-0.5 MPa, and the distance between the spray gun and the substrate is maintained at 15-20 cm to ensure the uniformity of the spraying; the rotation speed of the spin coating method is set at 1000-3000 rpm, and the spin coating time is 30-90 seconds, so that the coating thickness is accurately controlled within the set range.
[0027] Furthermore, the hot pressing method adopts a step-by-step pressing process, first pre-pressing for 10-20 minutes at a pressure of 1-2 MPa to initially fit the support body and the platinum foil, and then final pressing for 20-70 minutes at a pressure of 3-5 MPa to ensure that the two are tightly combined and the internal stress is evenly distributed, thereby improving the overall quality of the hydrogen permeable foil.
[0028] Furthermore, the hydrogen permeable foil after annealing is stored in a sealed container filled with argon at room temperature and pressure to prevent surface oxidation. The storage time can reach more than 6 months, during which the performance of the hydrogen permeable foil does not decay by more than 10%, ensuring that it can be put into use at any time.
[0029] Furthermore, during the performance test, the gas flow rate of the mixed gas simulation device is controlled at 10-50 ml / min, the pressure is controlled at 0.5-2 MPa, and the temperature is controlled at 25-50°C, simulating a variety of actual working conditions to comprehensively and accurately evaluate the hydrogen extraction performance, stability and reliability of the hydrogen permeable foil.
[0030] (III) Beneficial effects
[0031] Compared with the prior art, the present invention provides a method for preparing a hydrogen permeable foil, which has the following beneficial effects:
[0032] In the present invention, in terms of materials and structure, nano silicon, nano carbon and nano hollow carbon fiber are mixed in a specific ratio, and a support body is formed by ultrasonic dispersion and silica sol bonding through processes such as impregnation, spraying or spin coating, thereby improving the comprehensive performance of the material; the high purity and reasonable thickness of the platinum foil ensure efficient separation of hydrogen, and the step-by-step pressure application of the hot pressing method makes the support body and the platinum foil closely combined, thereby enhancing the stability of hydrogen transmission and the overall structural strength;
[0033] In terms of process stability, the parameters of each step are precisely controlled, such as the power, time and pause of ultrasonic treatment, parameter setting of coating method, pressure and time of hot pressing method, etc., which effectively avoids material damage and structural defects, ensuring stable process and easy operation;
[0034] The performance test phase simulates a variety of working conditions to comprehensively evaluate the hydrogen extraction performance, stability and reliability, providing strong data support for practical applications; the storage method after annealing treatment ensures material performance, extends service life, reduces maintenance costs and losses, making it extremely advantageous in hydrogen separation applications in the energy and chemical industries. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 is a flow chart of the method of the present invention;
[0036] Figure 2 This is a numerical comparison diagram between Example 1 and Example 2 of the present invention. DETAILED DESCRIPTION
[0037] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0038] Embodiment 1:
[0039] like Figure 1As shown, a method for preparing a hydrogen permeable foil provided by an embodiment of the present invention comprises the following steps:
[0040] S1. Preparation of support:
[0041] Nano-silicon, nano-carbon and nano-hollow carbon fiber were mixed in an organic solvent ethanol at a ratio of 5:3:2, and the mixed solution was ultrasonically treated using an ultrasonic dispersion device. The ultrasonic power was set to 300 W, the ultrasonic time was 60 minutes, and there was a 5-minute pause every 15 minutes. During this period, the solution temperature was regularly checked to maintain it at 40°C to ensure that each nanomaterial was evenly dispersed.
[0042] Slowly add 20% silica sol by mass into the dispersed solution, and stir continuously at a stirring speed of 500 rpm for 3 hours to fully mix the silica sol and the nanomaterial.
[0043] The mixed solution was coated on the ceramic sheet substrate material by dipping, and the substrate material was slowly immersed in the mixed solution at a speed of 2 cm / min for 45 seconds to form a precursor of the support body with a coating thickness of 5 μm.
[0044] The coated precursor is placed in an oven for drying at a temperature of 100° C. for 18 hours to volatilize the organic solvent and initially solidify the binder.
[0045] The dried support precursor is then placed in a high-temperature furnace for sintering at 500°C for 4 hours. During the sintering process, the silica sol further reacts to form a stable structure, and the nanomaterials are more tightly bonded, thereby forming a support with good performance.
[0046] S2. Assembly of hydrogen permeable foil:
[0047] The prepared support was compounded with a platinum foil with a purity of 99.97% and a thickness of 50 μm. The support was pre-pressed for 15 minutes at a pressure of 1.5 MPa at a temperature of 400°C under a pressure of 3 MPa, and then the support and the platinum foil were preliminarily bonded. The support was then finally pressed for 45 minutes at a pressure of 3 MPa to ensure that the two were tightly bonded and the internal stress was evenly distributed. The total hot pressing time was 60 minutes, which ensured that the interface between the support and the platinum foil was well bonded, which was beneficial to the transmission of hydrogen.
[0048] S3, post-processing:
[0049] The assembled hydrogen permeable foil is annealed at 700°C for 2 hours. Annealing in a hydrogen atmosphere can further activate the surface of the platinum foil and improve its ability to adsorb and catalyze the decomposition of hydrogen.
[0050] The prepared hydrogen permeable foil was subjected to a performance test. A mixed gas simulation device was used to control the gas flow rate at 30 ml / min, the pressure at 1.2 MPa, and the temperature at 35°C. A mixed gas containing hydrogen was passed through one side of the hydrogen permeable foil, and the permeated gas was collected on the other side. The content and purity of hydrogen in the permeated gas were detected by gas chromatography and other analytical methods to evaluate the performance of the hydrogen permeable foil.
[0051] The ultrasonic power and time are moderate, which is conducive to the uniform dispersion of nanomaterials and avoids excessive ultrasonication affecting the material structure; the dip coating operation is relatively simple and has low equipment requirements; the lower hot pressing pressure and temperature can reduce energy consumption and equipment loss to a certain extent; the various parameters are relatively mild, the overall process stability is good, and it is easy to operate and control.
[0052] Embodiment 2:
[0053] A method for preparing a hydrogen permeable foil comprises the following steps:
[0054] S1. Preparation of support:
[0055] The solution was ultrasonically treated with an ultrasonic power of 400 W for 75 min, with a 5-min pause after every 15 min of ultrasonication. The solution temperature was regularly checked and maintained at 45 °C to ensure uniform dispersion of the nanomaterials.
[0056] Slowly add 25% by mass silica sol into the dispersed solution, and stir at a speed of 600 rpm for 3.5 hours to fully mix the silica sol and the nanomaterial.
[0057] The mixed solution was coated on the metal sheet substrate material by spin coating, the spin coating speed was set at 2000 rpm, the spin coating time was 60 seconds, and the precursor of the support was formed, and the coating thickness was 7 μm.
[0058] The coated precursor was placed in an oven and dried at 110° C. for 20 hours to evaporate the organic solvent and initially solidify the binder.
[0059] Then, the dried support precursor is placed in a high-temperature furnace and sintered at 550° C. for 5 hours to allow the silica sol to react to form a stable structure and the nanomaterials to be tightly combined into a support.
[0060] S2. Assembly of hydrogen permeable foil:
[0061] Nano-silicon, nano-carbon and nano-hollow carbon fibers are mixed in an organic solvent ethanol at a ratio of 5:3:2, and the support is compounded with a platinum foil with a purity of 99.98% and a thickness of 70 μm using an ultrasonic dispersion device. Hot pressing is performed at a pressure of 4 MPa and a temperature of 450°C, with a pre-pressing of 1.8 MPa for 18 minutes and a final pressure of 4 MPa for 50 minutes, for a total of 68 minutes, to ensure good interface bonding for hydrogen transmission.
[0062] S3, post-processing:
[0063] The hydrogen permeable foil was annealed at 750°C for 2.5 hours to activate the surface of the platinum foil in a hydrogen atmosphere.
[0064] During the performance test, the gas flow rate of the mixed gas simulation device was set to 40 ml / min, the pressure was 1.6 MPa, and the temperature was 40°C. The hydrogen content and purity of the permeated gas were detected to evaluate the foil performance.
[0065] like Figure 1 As shown, in some embodiments, the substrate material is a ceramic sheet or a metal sheet;
[0066] Ceramic sheet as substrate material
[0067] High chemical stability: Under complex process conditions such as high-temperature sintering, hydrogen environment, and contact with various chemical reagents, the ceramic sheet can maintain its own stable chemical properties and is not easy to react chemically with nano-silicon, nano-carbon, nano-hollow carbon fiber, silica sol, platinum foil, etc., thereby ensuring the structural integrity and performance stability of the hydrogen permeation foil, and avoiding problems such as decreased hydrogen permeability or material failure due to chemical reactions of the base material.
[0068] Excellent high temperature resistance: In the high temperature links such as the sintering process of the support precursor (400-600℃) and the annealing treatment of the hydrogen permeable foil (600-800℃), the ceramic sheet can withstand high temperature without softening, deformation or decomposition, providing a stable support structure for the entire preparation process, ensuring the smooth progress of each process step, and helping to form high-quality hydrogen permeable foil.
[0069] Good electrical insulation: During the process of hydrogen adsorption, diffusion and penetration, the electrical insulation of the ceramic sheet can avoid problems such as current interference or electron transfer caused by the conductivity of the substrate material, which is beneficial to maintaining the stability of the physical and chemical effects between hydrogen and the material, ensuring that the selective permeability of hydrogen through the foil is not affected by electrical factors, and plays an important role in the precise control of the hydrogen separation process.
[0070] Metal sheet as base material
[0071] Good thermal conductivity: During hot pressing and lamination (300-500°C) and subsequent heat treatment, the metal sheet can quickly transfer heat, making the temperature distribution between the support and the platinum foil more uniform, promoting atomic diffusion and bonding between the two, improving the interface bonding strength, and facilitating the formation of a tightly connected hydrogen permeable foil structure, thereby enhancing the stability and efficiency of hydrogen transmission.
[0072] High mechanical strength and toughness: During the preparation and subsequent use of the hydrogen permeable foil, the metal sheet can provide strong mechanical support for the entire structure, resist external stress and mechanical shock, prevent the hydrogen permeable foil from being damaged by external forces such as rupture, delamination or deformation, and extend its service life. It is especially suitable for use in harsh mechanical environments or in application scenarios that require frequent handling and installation.
[0073] Strong machinability: Metal sheets can be easily made into various shapes and sizes through cutting, rolling, stamping and other processing techniques, which can meet the diverse requirements of the shape and size of hydrogen permeable foil in different application scenarios, provide convenience for large-scale industrial production and customized production, and improve production efficiency and product applicability.
[0074] like Figure 1 As shown, in some embodiments, the platinum foil has a purity of more than 99.95%, and the initial thickness of the platinum foil is between 10-100 μm. It is used as the main functional layer for hydrogen permeation because platinum has good adsorption and catalytic decomposition capabilities for hydrogen, and can promote the separation of hydrogen in the mixed gas;
[0075] High-purity platinum can minimize the interference of impurities on the hydrogen adsorption and catalytic decomposition process. Impurity atoms may occupy the active sites on the platinum surface, hinder the adsorption of hydrogen molecules, or change the electronic structure of platinum, affecting its catalytic activity for hydrogen. For example, some metal impurities may form relatively stable compounds with hydrogen, reducing the desorption rate of hydrogen, thereby affecting the overall penetration efficiency of hydrogen through the foil. Platinum with a purity of more than 99.95% can provide abundant and pure active sites, ensuring that hydrogen molecules can be efficiently adsorbed on its surface and quickly decomposed into hydrogen atoms under catalysis, accelerating the penetration process of hydrogen in the foil;
[0076] Hydrogen permeation path and efficiency: Within the thickness range of 10-100μm, it can ensure that there is enough material thickness to maintain structural stability and that hydrogen can be effectively permeated under reasonable time and pressure gradients. Thinner platinum foil (such as close to 10μm) can shorten the hydrogen diffusion path, reduce the transmission time of hydrogen molecules in the foil, and increase the initial permeation rate of hydrogen to a certain extent. However, too thin foil may lack mechanical strength and be easily damaged during the preparation process or actual use, affecting its service life and stability.
[0077] Cost and performance balance: On the other hand, although thicker platinum foil (such as close to 100μm) has higher mechanical strength, it will increase material costs and may reduce permeation efficiency due to the long hydrogen diffusion path. Within this thickness range, optimization and selection can be made according to specific application scenarios and performance requirements. For example, in a small laboratory test device with high requirements for hydrogen flux and a relatively stable mechanical environment, a thinner platinum foil can be used; in hydrogen separation equipment that is mass-produced in industry and may face certain mechanical shocks, the thickness can be appropriately increased to ensure stability, while maintaining a high hydrogen permeation performance by optimizing other process parameters, thereby achieving an ideal balance between cost and performance.
[0078] In summary, the high purity and appropriate thickness of platinum foil are key factors in achieving efficient hydrogen separation, and play an indispensable role in the performance of hydrogen permeation foil.
[0079] Higher ultrasonic power and longer ultrasonic time may make the nanomaterials more evenly dispersed; higher silica sol mass fraction, stirring speed and time may enhance the bonding between nanomaterials and silica sol; spin coating may have more advantages in controlling the uniformity of coating thickness; higher platinum foil purity and thickness may increase the upper limit of hydrogen permeation performance of foil; higher hot pressing pressure and temperature as well as annealing temperature and time may make the support and platinum foil bond more tightly and the platinum foil surface activation effect better, thereby improving hydrogen permeation performance.
[0080] like Figure 1 As shown, in some embodiments, the mass fraction of the silica sol is between 10% and 30%;
[0081] Adhesion performance and structural stability
[0082] When the mass fraction of silica sol is between 10% and 30%, it can provide a moderate bonding effect for nano-silicon, nano-carbon and nano-hollow carbon fibers. At a lower mass fraction (such as close to 10%), the bonding force is relatively weak, and in the subsequent drying and sintering process, the position of the nano-material may not be effectively fixed, resulting in the agglomeration of the nano-material or its detachment from the base material, affecting the structural uniformity and integrity of the support, thereby reducing the performance of hydrogen permeation foil. For example, when coating the precursor after ultrasonic dispersion, if the silica sol has insufficient bonding force, the nano-material may re-aggregate in the solution, causing uneven distribution of the components of the coating layer, affecting the diffusion path of hydrogen in the support.
[0083] As the mass fraction increases, the bonding effect is enhanced, but when it exceeds 30%, the silica sol may over-fill the gaps between the nanomaterials, forming too much amorphous silicon dioxide during the drying and sintering process, obstructing the gas diffusion channel, and increasing the brittleness of the support, making it easy to crack in subsequent processes such as hot pressing, affecting the overall quality and performance stability of the hydrogen permeable foil.
[0084] Impact on hydrogen transmission performance
[0085] Within the appropriate mass fraction range, the silica network structure formed by the silica sol after sintering can adjust the porosity and pore size distribution of the support to a certain extent. When the mass fraction is close to 10%, the formed network is relatively loose, which may lead to excessive porosity of the support, and the diffusion path of gas molecules in it becomes longer and disordered, which is not conducive to the rapid and efficient transmission of hydrogen; when the mass fraction is close to 30%, the network structure is too dense, which will reduce the porosity and pore size, increase the resistance to hydrogen diffusion, and reduce the hydrogen permeation rate. Between 10%-30%, the microstructure of the support can be optimized by adjusting the mass fraction of silica sol to make it have a suitable porosity and pore size, promote the adsorption, diffusion and penetration of hydrogen in the support, and thus improve the hydrogen separation performance of the hydrogen permeation foil.
[0086] like Figure 1 As shown, in some embodiments, during the ultrasonic treatment, the ultrasonic treatment is paused for 5 minutes every 15 minutes to prevent the solution from being locally overheated due to continuous ultrasonic treatment, thereby affecting the dispersion effect and structural stability of the nanomaterials. At the same time, the solution temperature is regularly checked to maintain it between 30-50°C;
[0087] In the preparation process of hydrogen permeable foil, the pause and temperature control measures during ultrasonic treatment are crucial. Continuous ultrasound can easily cause local overheating of the solution, which will change the chemical environment of the nanomaterial. For example, too high a temperature may change the active groups on the surface of nanosilicon, affecting its ability to bind with other nanomaterials and silica sol, thereby destroying the overall dispersion effect, causing the nanomaterial to agglomerate, and changing the microstructure and performance of the support.
[0088] Pausing for 5 minutes every 15 minutes of ultrasound can effectively avoid excessive heat accumulation. At the same time, maintaining the solution temperature between 30-50°C can ensure that the nanomaterials are in a suitable dispersion environment. Within this temperature range, the electrical properties of nanocarbon and the structural stability of nano hollow carbon fibers are maintained, which is conducive to their synergistic effect. For example, nanocarbon can better assist the adsorption and conduction of hydrogen at a suitable temperature, and the hollow structure of nano hollow carbon fibers can also stably provide a channel for hydrogen transmission, thereby ensuring the performance of the support body, laying the foundation for the subsequent high-quality preparation of hydrogen permeable foil, and ensuring its efficient and stable operation during the hydrogen separation process.
[0089] like Figure 1 As shown, in some embodiments, the dipping method is specifically to slowly immerse the substrate material into the mixed solution at a speed of 1-3 cm / min, and the dipping time is 30-60 seconds to ensure that the solution is evenly attached to the surface of the substrate; the spraying pressure of the spraying method is controlled at 0.2-0.5 MPa, and the distance between the spray gun and the substrate is maintained at 15-20 cm to ensure the uniformity of the spraying; the rotation speed of the spin coating method is set at 1000-3000 rpm, and the spin coating time is 30-90 seconds, so that the coating thickness is accurately controlled within the set range;
[0090] Dipping method
[0091] Importance of slow immersion speed: Slowly immersing the substrate material into the mixed solution at a speed of 1-3cm / min can give the solution enough time to fully infiltrate and diffuse on the substrate surface. If the speed is too fast, the solution may not have enough time to evenly adhere to the substrate, which may easily form local effusion or uneven thickness, resulting in uneven composition and structure of the support precursor, affecting the subsequent hydrogen transmission performance in the support. For example, at an immersion speed that is too fast, nanomaterials may accumulate on the substrate surface, resulting in reduced porosity in local areas and obstructing the diffusion path of hydrogen.
[0092] The influence of appropriate immersion time: The immersion time is between 30-60 seconds. This period of time can ensure that the substrate fully absorbs the nanomaterials and silica sol in the solution to form a uniform and stable precursor coating. Too short a time will lead to insufficient adsorption, insufficient nanomaterial content in the coating, and affect the performance of the support; while too long a time may make the coating too thick, which is prone to cracking or falling off during the drying and sintering process, which is also not conducive to the quality of the support.
[0093] Spraying method
[0094] The role of spraying pressure: The spraying pressure is controlled at 0.2-0.5MPa. Within this pressure range, the solution can be sprayed onto the substrate at a suitable speed and droplet size. If the pressure is too low, the solution atomization effect is poor, and large droplets may be formed, resulting in uneven spraying, inconsistent coating thickness and material agglomeration; if the pressure is too high, the solution spray speed is too fast, which may cause part of the solution to rebound or blow away, resulting in material waste and failure to ensure uniform coating on the substrate surface, affecting the quality and performance of the support precursor.
[0095] The influence of the distance between the spray gun and the substrate: The distance between the spray gun and the substrate is kept at 15-20cm. This distance can ensure that the solution maintains a good dispersion state and appropriate impact force when it reaches the substrate. If the distance is too close, the impact force of the solution is too large, which may damage the flatness of the substrate surface or redistribute the coated material; if the distance is too far, the solution may partially evaporate or disperse unevenly during the flight process, resulting in uneven coating thickness and composition deviation, which in turn affects the performance of the support.
[0096] Spin coating method
[0097] Control of coating thickness by rotation speed: The rotation speed of the spin coating method is set at 1000-3000rpm. Within this rotation speed range, the solution can be evenly coated on the substrate through centrifugal force, and the coating thickness can be accurately controlled. When the rotation speed is low, the solution cannot be fully spread and evenly distributed, and the coating thickness is uneven and may be too thick; when the rotation speed is too high, the solution may be excessively thrown out of the substrate, resulting in a coating thickness that is too thin and unable to form a complete support precursor coating, affecting the preparation quality and performance of the hydrogen permeable foil.
[0098] The significance of spin coating time: The spin coating time is 30-90 seconds, which can ensure that the solution is fully dried and solidified at the set speed to form a stable coating structure. If the time is too short, the coating may not be completely dry, and it is easy to deform or fall off during the subsequent processing; if the time is too long, the coating may crack or reduce the bonding strength with the substrate due to excessive drying, affecting the quality and stability of the support.
[0099] like Figure 1 As shown, in some embodiments, the hot pressing method adopts a step-by-step pressing process, first pre-pressing for 10-20 minutes at a pressure of 1-2 MPa to initially fit the support body and the platinum foil, and then final pressing for 20-70 minutes at a pressure of 3-5 MPa to ensure that the two are tightly combined and the internal stress is evenly distributed, thereby improving the overall quality of the hydrogen permeable foil;
[0100] Pre-pressing stage (1-2MPa, 10-20 minutes)
[0101] Initial bonding: Pre-pressing for 10-20 minutes at a relatively low pressure of 1-2MPa can gradually bring the support and platinum foil closer and initially bond under relatively mild conditions. The pressure at this stage should not be too high. If the pressure is too high, the support or platinum foil may be partially deformed or damaged due to sudden strong squeezing. Especially for the support composed of nanomaterials, excessive pressure may destroy its internal structure and affect the formation of hydrogen transmission channels. For example, it may cause the nano hollow carbon fibers to break or the nano silicon particles to agglomerate, reducing the performance of the support.
[0102] Gas discharge and stress buffering: Appropriate pre-pressing time and pressure help to discharge air and other gases between the support and the platinum foil, reduce internal gaps, and create better conditions for subsequent tight bonding. At the same time, the low-pressure pre-pressing process can give the material a certain amount of time to adjust its own structure, buffer the stress impact caused by subsequent high pressure, avoid problems such as material delamination or cracking caused by stress concentration at the final pressure, and ensure the structural integrity of the hydrogen permeating foil.
[0103] Final pressure stage (3-5MPa, 20-70 minutes)
[0104] Tight bonding effect: The support and platinum foil can be tightly bonded at a high pressure of 3-5MPa for 20-70 minutes. The high pressure promotes the mutual diffusion and bonding between the atoms of the materials, enhances the interface bonding strength, ensures that hydrogen can be smoothly transmitted at the interface between the two, and reduces the resistance to hydrogen penetration. For example, platinum atoms may diffuse to the surface of the nanomaterial of the support, forming a more stable connection structure, and improving the overall performance of hydrogen permeation foil.
[0105] Advantages of uniform stress distribution: Sufficient final pressure time can make the internal stress evenly distributed in the material. If the final pressure time is too short, the internal stress of the material cannot be fully released and evenly distributed, which may cause the hydrogen permeable foil to deform and degrade due to local stress concentration during use. By reasonably controlling the final pressure time and pressure, it is ensured that the support body and the platinum foil are tightly combined and the internal stress is uniform, thereby improving the mechanical stability and hydrogen separation performance of the hydrogen permeable foil, extending its service life, and enabling it to work stably and efficiently in practical applications.
[0106] like Figure 1 As shown, in some embodiments, the hydrogen permeable foil after annealing is stored in a sealed container filled with argon at room temperature and pressure to prevent oxidation of its surface. The storage time can reach more than 6 months, during which the performance of the hydrogen permeable foil does not decay by more than 10%, ensuring that it can be put into use at any time; in the post-processing link of the hydrogen permeable foil, the storage conditions after annealing are crucial. Placing it in a sealed container filled with argon is to use the inertness of argon to effectively isolate oxygen. At room temperature and pressure, oxygen easily undergoes oxidation reaction with the surface of metals such as platinum to form an oxide film, which greatly hinders the adsorption and catalytic decomposition of hydrogen. For example, after the platinum surface is oxidized, its active sites are occupied by oxides, and hydrogen molecules are difficult to attach and decompose, which seriously reduces the performance of the hydrogen permeable foil.
[0107] This storage method can ensure that the storage time is more than 6 months and the performance degradation does not exceed 10%, so that the hydrogen permeable foil can be put into use at any time. During long-term storage, the stable storage environment avoids material structure damage or performance degradation caused by oxidation, moisture or other impurity contamination. This is of great significance for practical applications. Whether in laboratory research or industrial production, it can ensure that the hydrogen permeable foil maintains a good working condition when needed, reduce the risk of experimental errors or production interruptions caused by fluctuations in material properties, improve the reliability and stability of the entire hydrogen separation process, and reduce maintenance costs and material losses.
[0108] like Figure 1 As shown, in some embodiments, during the performance test, the gas flow rate of the mixed gas simulation device is controlled at 10-50 ml / min, the pressure is controlled at 0.5-2 MPa, and the temperature is controlled at 25-50° C., simulating a variety of actual working conditions to comprehensively and accurately evaluate the hydrogen extraction performance, stability and reliability of the hydrogen permeation foil;
[0109] Gas flow rate (10-50ml / min)
[0110] The role of the low flow rate range (10-30ml / min): At lower flow rates, such as 10-30ml / min, hydrogen molecules have relatively sufficient time to fully contact and react with the surface of the hydrogen permeable foil. This helps to accurately evaluate the foil's ability to adsorb and permeate hydrogen under low flow conditions close to actual applications. For example, in some small hydrogen separation experimental devices or fine chemical processes with low hydrogen flux requirements, lower gas flow rates are common conditions. By testing in this flow rate range, the hydrogen extraction efficiency and selectivity of the hydrogen permeable foil in this case can be determined, providing accurate performance data for its application in similar scenarios.
[0111] The significance of the high flow rate range (30-50ml / min): When the gas flow rate is increased to 30-50ml / min, it can simulate the gas processing scene with a larger flow rate in industrial production. Under this condition, the stability of the hydrogen permeation foil under high flow impact and the hydrogen separation performance can be observed. Higher flow rates will increase the impact and shear force of gas molecules on the foil surface, testing its structural integrity and long-term reliability. At the same time, it can also reflect the flux limit and separation effect of the hydrogen permeation foil under high flow conditions, providing an important reference for its feasibility in large-scale industrial applications.
[0112] Pressure (0.5-2MPa)
[0113] Influence of low pressure range (0.5-1MPa): In a low pressure environment of 0.5-1MPa, the movement of hydrogen molecules is relatively slow, and the interaction time with the foil surface is longer. This helps to study the adsorption kinetics and permeation mechanism of hydrogen permeation foil under low pressure conditions. For example, in some laboratory research or small energy equipment with low pressure requirements, low pressure conditions are more common. By testing in this pressure range, we can gain a deep understanding of the performance characteristics of hydrogen permeation foil under low pressure and optimize its use conditions in low pressure application scenarios.
[0114] The role of the high pressure range (1-2MPa): When the pressure rises to 1-2MPa, the concentration and activity of hydrogen molecules increase, and the penetration pressure on the foil also increases. This can simulate the high-pressure gas separation process in industrial production and test the pressure resistance and hydrogen separation performance of hydrogen permeation foil under high pressure environment. Under high pressure, the foil may face problems such as structural deformation and changes in material permeability. Through testing, its reliability and stability under high pressure conditions can be determined, providing key data for its design and use in high-pressure industrial applications.
[0115] Temperature (25-50℃)
[0116] The significance of the low temperature section (25-35°C): The temperature range of 25-35°C is close to the normal temperature environment, which can reflect the performance of hydrogen permeation foil under daily working conditions. This temperature range can be used to evaluate the hydrogen extraction performance and stability of foil in a conventional environment, and provide basic performance data for its application in general industrial and civil fields. At the same time, at this temperature, the physical and chemical properties of the material are relatively stable, which is convenient for accurately analyzing the interaction mechanism between hydrogen and foil.
[0117] Impact of high temperature section (35-50℃): When the temperature rises to 35-50℃, some application scenarios in higher temperature environments can be simulated, such as hot gas separation in certain chemical processes or hydrogen processing in energy equipment operating in high temperature environments. At higher temperatures, the properties of materials may change, such as the structural stability of nanomaterials, the catalytic activity of platinum, etc. By testing in this temperature range, we can understand the performance change trend and reliability of hydrogen permeable foil in high temperature environments, and provide guidance and restrictions for its use in high temperature application scenarios.
[0118] By conducting comprehensive performance tests within the above-mentioned gas flow rate, pressure and temperature ranges, a variety of actual working conditions can be simulated to accurately and comprehensively evaluate the hydrogen extraction performance, stability and reliability of the hydrogen permeable foil, providing sufficient technical support and performance guarantee for its application in different fields.
[0119] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a hydrogen permeable foil, characterized in that: The method comprises the following steps: S1. Preparation of support: Mix nano-silicon, nano-carbon and nano-hollow carbon fiber in an organic solvent ethanol at a ratio of 5:3:2, and use an ultrasonic dispersion device to ultrasonically treat the mixed solution, with an ultrasonic power between 100-500W and an ultrasonic time of 30-90 minutes to ensure that each nanomaterial is evenly dispersed; Slowly add silica sol to the dispersed solution while stirring continuously. The stirring speed is controlled between 300-800rpm. Stir continuously for 2-4 hours to fully mix the silica sol and the nanomaterial. The mixed solution is coated on the substrate material by dipping, spraying or spin coating to form a precursor of the support, and the coating thickness can be between 1-10 μm; The coated precursor is placed in an oven for drying at a temperature between 80 and 120°C for 12 to 24 hours to volatilize the organic solvent and initially solidify the binder; The dried support precursor is then placed in a high-temperature furnace for sintering at a temperature between 400-600°C for 2-6 hours. During the sintering process, the silica sol further reacts to form a stable structure, and the nanomaterials are more tightly bonded, thereby forming a support with good performance. S2. Assembly of hydrogen permeable foil: The prepared support is compounded with the platinum foil, and the support is tightly combined with the platinum foil by hot pressing at a pressure of 1-5 MPa and a temperature of 300-500°C. The hot pressing time is 30-90 minutes, so as to ensure good interface bonding between the support and the platinum foil, which is conducive to the transmission of hydrogen; S3, post-processing: Annealing the assembled hydrogen permeable foil at a temperature between 600 and 800° C. for 1 to 3 hours. Annealing in a hydrogen atmosphere can further activate the surface of the platinum foil and improve its ability to adsorb and catalyze decomposition of hydrogen. The prepared hydrogen permeable foil was subjected to a performance test. A mixed gas containing hydrogen was passed into one side of the hydrogen permeable foil using a mixed gas simulation device, and the permeated gas was collected on the other side. The content and purity of hydrogen in the permeated gas were detected by gas chromatography and other analytical methods to evaluate the performance of the hydrogen permeable foil.
2. The method for preparing a hydrogen permeable foil according to claim 1, characterized in that: The base material is a ceramic sheet or a metal sheet.
3. The method for preparing a hydrogen permeable foil according to claim 1, characterized in that: The platinum foil has a purity of more than 99.95% and an initial thickness of 10-100 μm. It serves as the main functional layer for hydrogen permeation because platinum has good adsorption and catalytic decomposition capabilities for hydrogen and can promote the separation of hydrogen in mixed gases.
4. The method for preparing a hydrogen permeable foil according to claim 1, characterized in that: The mass fraction of the silica sol is between 10% and 30%.
5. The method for preparing a hydrogen permeable foil according to claim 1, characterized in that: During the ultrasonic treatment, the solution was treated for 15 minutes and then paused for 5 minutes to prevent local overheating of the solution due to continuous ultrasonic treatment, which would affect the dispersion effect and structural stability of the nanomaterials. The solution temperature was checked regularly to maintain it between 30-50°C.
6. The method for preparing a hydrogen permeable foil according to claim 1, characterized in that: Specifically, the immersion method comprises the following steps: slowly immersing the substrate material into the mixed solution at a speed of 1-3 cm / min for 30-60 seconds to ensure that the solution is evenly attached to the surface of the substrate; the spraying pressure of the spraying method is controlled at 0.2-0.5 MPa, and the distance between the spray gun and the substrate is maintained at 15-20 cm to ensure the uniformity of the spraying; the rotation speed of the spin coating method is set at 1000-3000 rpm, and the spin coating time is 30-90 seconds, so that the coating thickness is accurately controlled within the set range.
7. The method for preparing a hydrogen permeable foil according to claim 1, characterized in that: The hot pressing method adopts a step-by-step pressing process, first pre-pressing for 10-20 minutes at a pressure of 1-2 MPa to initially fit the support body and the platinum foil, and then final pressing for 20-70 minutes at a pressure of 3-5 MPa to ensure that the two are tightly combined and the internal stress is evenly distributed, thereby improving the overall quality of the hydrogen permeable foil.
8. The method for preparing a hydrogen permeable foil according to claim 1, characterized in that: The hydrogen permeable foil after annealing is stored in a sealed container filled with argon at room temperature and pressure to prevent surface oxidation. The storage time can reach more than 6 months, during which the performance of the hydrogen permeable foil does not decay by more than 10%, ensuring that it can be put into use at any time.
9. The method for preparing a hydrogen permeable foil according to claim 1, characterized in that: During the performance test, the gas flow rate of the mixed gas simulation device is controlled at 10-50 ml / min, the pressure is controlled at 0.5-2 MPa, and the temperature is controlled at 25-50°C, simulating a variety of actual working conditions to comprehensively and accurately evaluate the hydrogen extraction performance, stability and reliability of the hydrogen permeation foil.